Prenatal ultrasound phenotype of fetuses with recurrent 1q21.1 deletion and duplication syndrome - Wang, Fengyang; Peng, Huijuan; Lou, Guiyu; Ren, Yanxin; Liao, Shixiu (Frontiers in Pediatrics, 2025)
ObjectiveOur study aimed to collect fetuses with recurrent 1q21.1 deletion or duplication syndrome for systematic clinical phenotype analysis to further delineate the intrauterine phenotype features of the two reciprocal syndromes.MethodsPrenatal samples, including amniotic fluid and chorionic villus samples, were obtained by amniocentesis and chorionic villus sampling at our center, respectively. In total, 43 fetuses were diagnosed with recurrent 1q21.1 deletion or duplication syndrome via array comparative genomic hybridization (array CGH) or copy number variation sequencing (CNV-seq). Prenatal clinical data, pregnancy outcomes, and individual conditions after birth were collected.ResultsIn total, 20 fetuses were diagnosed with 1q21.1 deletion syndrome, and 11 had abnormal ultrasound findings. The most common ultrasound features were renal anomalies, musculoskeletal abnormalities, and increased NT. Other less common ultrasound findings encompassed neurologic abnormalities, cardiovascular defects, absence of the gallbladder, intrauterine growth retardation, and cervical cystic hygroma. On the other hand, 23 fetuses had reciprocal 1q21.1 duplication syndrome, 11 of which had abnormal ultrasound findings, mainly nasal bone abnormalities, cardiovascular defects, increased NT, and neurologic abnormalities.ConclusionsOur case study suggested that the prenatal clinical phenotypes of the recurrent 1q21.1 deletion syndrome and reciprocal duplication syndrome fetuses were highly diverse with incomplete penetrance. Additionally, our findings should expand the intrauterine phenotype associated with the recurrent 1q21.1 region by a series of prenatal ultrasonic anomalies in this work that were described for the first time, which might broaden knowledge of the genotype and phenotype correlation.